Differences In Supervisors' Interpersonal Communication On The Ability To Complete A Thesis - Sudarsono, Sudarsono; Kusmawati, Wiwik; Ernata, Yusvidha; Setyawan, Trinovandhi; Irawan, Dedy; Azhar Nuh, Fuad (JUPE : Jurnal Pendidikan Mandala, 2024)
The aim of this research is to determine the differences in interpersonal communication between supervisors and their ability to complete a thesis. The research method is a quasi-experimental method. The sampling technique was simple random sampling. The sample is Class 2019 class C students as the experimental class and Class 2019 class D students as the control class. The data collection technique uses tests and non-tests. The instruments are objective tests of the multiple choice type and non-test instruments in the form of questionnaires. The data obtained were analyzed using the prerequisite normality test and homogeneity test. The results of the t-test which was carried out with the SPSS program, showed that the tcount value was greater than the ttable value, meaning that there was a significant difference in the ability to complete the thesis of experimental class and control class students, so it could be concluded that there was a difference in the supervisor's interpersonal communication on the ability to complete thesis.